Da'wah and Commodification of Religion in West Java Broadcasting Institutions - Tabroni, Roni; Hantoro, Naditha Rizkya; Shabana, Amin (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2025)
This research aims to analyze the ideology underlying the operation of religion-based broadcasting institutions and how the process of commodification of da'wah occurs in West Java. Using a qualitative approach and case studies, this study examines three Broadcasting Institutions in Bandung, Cirebon, and Tasikmalaya, which were selected based on their active involvement in da'wah broadcasting and wide audience reach. Data was obtained through in-depth interviews, field observations, and analysis of the content of the da'wah program for six months. The results of the study show that da'wah has undergone a transformation from a spiritual function to a media product that is packaged according to market interests and dominant ideologies. Commodification occurs in three aspects: broadcast content, audiences as commodities and sources of funds, and media labor that acts as a capitalistic production apparatus. This research confirms that Broadcasting Institutions in West Java not only prioritize educational functions in da'wah, but also make religion an economic and ideological instrument to maintain its existence in the midst of competition in the broadcasting industry. These findings contribute to the study of the political economy of the media and become an important reference for policymakers in balancing commercial interests and da'wah functions in the media.